A Prospective Interventional Study in Chronic Prostatitis with Emphasis to Clinical Features - Stamatiou, Konstantinos Nikolaos; Moschouris, Hippocrates (Urology Journal, 2014)
Purpose: Chronic bacterial prostatitis displays a variety of symptoms (mainly local pain exhibiting variability in origin and intensity). These symptoms often persist despite bacterial eradication. The purpose of this article is to exam the role of phytotherapeutic agents as complementary treatment in patients with bacterial prostatitis. Materials and Methods: The material consisted of individuals with reported pelvic discomfort and genital pain with or without lower urinary tract symptoms (LUTS) and sexual dysfunction visiting our department from March 2009 to March 2011. Patients underwent Stamey-Meares test (several cases underwent the two glass test). Depending on history and specific symptoms urethral smear and semen cultures were additionally obtained from several patients. All patients were randomized into two groups. Subjects in the first group (72 patients) received appropriate antibiotic (according to the sensitivity test) for 15 days, while subjects in the second group (72 patients) received phytotherapeutic agents for 30 days, additionally the conventional 15 days antibiotic treatment. The response was tested using laboratory and clinical criteria. Results: We found no statistically significant differences between the two groups regarding bacterial and symptom persistence rate, however, symptoms burden was lower in patients receiving combinational treatment. Conclusion: Phytotherapeutic agents may improve pain and prostatitis related difficulty in urination. Further randomized, placebo-controlled studies are needed to substantiate safer conclusions.